DIKOTOMI PENDIDIKAN DALAM PANDANGAN PENDIDIKAN ISLAM - Lani Rahmawati; Manpan Drajat (Fakultas Agama Islam Universitas Wiralodra, 2022)
THE DICHOTOMY OF EDUCATION IN ISLAMIC EDUCATION This paper tries to analyze the tendency of the dichotomy that occurs in Islamic scholarship, this dichotomy is reflected in the style of the dichotomy of education. The demarcating separation between Religious and Non-Religious Sciences or what is called the dichotomization of knowledge in the discourse of Islamic education has caused a lot of debate among Islamic education leaders. Some figures fully support the dichotomy system and some strongly reject the dichotomy. This paper aims to describe the historical roots of the dichotomization of Islamic education. These findings indicate that Islam strongly recommends scientific exploration by not separating and contrasting religious and non-religious sciences. In Islam there is no dichotomy of knowledge, only the clarification of knowledge, but in practice the classification of knowledge is misinterpreted by many Muslim communities themselves